Human Umbilical Cord Blood Derived (HUCB) Mesenchymal Stem Cells (MSc’s) As an Alternative Therapeutics in Managing Infections - Madhushree R, Madhushree R; A.B, Jolitha; Ranjitha A, Ranjitha A; Smitha N, Smitha N; K R, Manjula (Journal of Neonatal Surgery, 2025)
Umbilical cord blood (UCB), considered medical waste, contains Mesenchymal stem cells (MSCs) in a mucous connective tissue known as Wharton’s jelly. These cells exhibit the ability to self-renew and maintain multipotency while differentiating into various lineages. UCB provides a non-invasive and ethically uncomplicated source for MSC and UC-derived MSCs (UC-MSCs) are particularly valuable due to their immunomodulatory properties, making them promising candidates for regenerative medicine and immunotherapy. This study aims to explore the current understanding of UC-MSCs, their differentiation potential, clinical applications, and the challenges faced in MSC therapy. The emergence of mesenchymal stem cells (MSCs) as a potential antimicrobial agent was also done. An attempt to optimize the culture conditions, cell sourcing, and standardization of protocols to maximize their therapeutic efficacy.